Transitional Meningioma in a Dog - Guedes, Paula Elisa Brandão; Oliveira Cruz, Thais Nascimento de Andrade; Deiró, Ana Graziela; Silva, Juneo Freitas; Said, Roueda Abou; Lessa Silva, Fabiana; Alberto Carlos, Renata Santiago (Acta Scientiae Veterinariae, 2019)
Background: Dogs and cats are the most common domestic animal species diagnosed with primary neoplasms of the central nervous system. Of these, meningioma is the brain tumor most commonly reported in dogs and is associated with several neurological changes, such as seizures. The ante mortem diagnosis is difficult to make because the use of computerized tomography, the gold standard for the presumptive diagnosis of brain tumors, is still a limited and expensive exam in veterinary medicine. The aim of this study is to report the case of a grade II transitional meningioma in a female dog attended and necropsied at the Veterinary Hospital of the Universidade Estadual de Santa Cruz (HV-UESC). Case: A 13-year-old female poodle was examined at HV-UESC with a clinical history of prostration, apathy, anorexia, partial vision loss, and neurological abnormalities, including seizures. The dog was being treated with phenobarbital (2 mg/kg three times a day) for seizures and doxycycline (5 mg/kg twice a day) for anaplasmosis diagnosed prior to clinical care at HV-UESC. On physical examination, the dog was observed to be mentally altered, with increased aggression, walking in large circles to the left, tremors and spasticity of the thoracic limbs. Laboratory analysis revealed a normal complete blood count. Biochemical analysis revealed an increase in alanine aminotransferase (296 U/mL), alkaline phosphatase (286 U/mL) and urea (121 mg/dL) levels. Based on the clinical and laboratory abnormalities, the suspicion of cerebral degenerative neuropathy or neoplasia was established. The dog was examined again approximately two months after initial presentation and no improvement in the dog’s neurological condition was noted; in fact, the dog´s condition had deteriorated, which was evidenced by worsening seizures, tetraparesis and bedsores. Due to the severity of the neurological changes, euthanasia was performed. After authorization from the owner, the dog was referred to the HV-UESC Necropsy Department, where the dog was necropsied. The primary macroscopic finding was a well-defined mass measuring approximately 2.5x1.5x1.5 cm in the frontal cortex of the left cerebral hemisphere. The lesion was firm and white with an irregular surface and was adhered to the dura mater. The mass compressed the adjacent brain tissue. Histopathological analysis demonstrated a non-encapsuled, expansive, and partially delimited neoplasm characterized by sheets of meningoendothelial cells arranged primarily in mantles, though sometimes in lobes, in two distinct patterns: meningoendothelial and fibrous. In addition, a moderate amount of psammomatous bodies were observed. These microscopic characteristics led to the diagnosis of a grade II transitional meningioma. Discussion: This report describes a case of meningioma in a female dog, which is the most common type of brain tumor diagnosed in dogs according to the literature. The affected animal was advanced in age, a factor that is associated with an increased risk of developing this neoplasm. The neurological alterations noted in this report were associated with the neoplastic process. The macroscopic finding of a cerebral neoformation was suggestive of neoplasm; this was confirmed by microscopic evaluation of the mass. As has been previously reported, the clinical neurological signs of most cases of suspected brain tumors occur late in the disease process, at which point the neoplasm is already in an advanced stage of development. Thus, the prognosis of the affected animal is poor, as it was in this case, which leads to euthanasia. In summary, this is a report of a case of intracranial transitional meningioma accompanied by progressive neurological alterations, in which an ante mortem diagnosis is difficult due to the limited use of computerized tomography in routine veterinary practice. <pre style="text-align: justify; line-height: 200%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Background: Dogs and cats are the most common domestic animal species diagnosed with primary neoplasms of the central nervous system. Of these, meningioma is the brain tumor most commonly reported in dogs and is associated with several neurological changes, such as seizures. The ante mortem diagnosis is difficult to make because the use of computerized tomography, the gold standard for the presumptive diagnosis of brain tumors, is still a limited and expensive exam in veterinary medicine. The aim of this study is to report the case of a grade II transitional meningioma in a female dog attended and necropsied at the Veterinary Hospital of the Universidade Estadual de Santa Cruz (HV-UESC). <pre style="text-align: justify; line-height: 200%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Case: A 13-year-old female poodle was examined at HV-UESC with a clinical history of prostration, apathy, anorexia, partial vision loss, and neurological abnormalities, including seizures<span style="font-size: 12pt; line-height: 200%; font-family: ’Times New Roman’, serif; color: #212121; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">. The dog was being treated with phenobarbital (2 mg/kg three times a day) for seizures and doxycycline (5 mg/kg twice a day) for anaplasmosis diagnosed prior to clinical care at HV-UESC. On physical examination, the dog was observed to be mentally altered, with increased aggression, walking in large circles<span style="font-size: 12pt; line-height: 200%; font-family: ’Times New Roman’, serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">to the left, tremors and spasticity of the thoracic limbs. Laboratory analysis revealed a normal complete blood count. Biochemical analysis revealed an increase in alanine aminotransferase (296 U/mL), alkaline phosphatase (286 U/mL) and urea (121 mg/dL) levels. Based on the clinical and laboratory abnormalities, the suspicion of cerebral degenerative neuropathy or neoplasia was established. The dog was examined again approximately two months after initial presentation and no improvement in the dog’s neurological condition was noted; in fact, the dog´s condition had deteriorated, which was evidenced by worsening seizures, tetraparesis and bedsores. Due to the severity of the neurological changes, euthanasia was performed. After authorization from the owner, the dog was referred to the HV-UESC Necropsy Department, where the dog was necropsied. The primary macroscopic finding was a well-defined mass measuring approximately 2.5x1.5x1.5 cm in the frontal cortex of the left cerebral hemisphere. The lesion was firm and white with an irregular surface and was adhered to the dura mater. The mass compressed the adjacent brain tissue. Histopathological analysis demonstrated a non-encapsuled, expansive, and partially delimited neoplasm characterized by sheets of meningoendothelial cells arranged primarily in mantles, though sometimes in lobes, in two distinct patterns: meningoendothelial and fibrous. In addition, a moderate amount of psammomatous bodies were observed. These microscopic characteristics led to the diagnosis of a grade II transitional meningioma. <pre style="text-align: justify; line-height: 200%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">Discussion: This report describes a case of meningioma in a female dog, which is the most common type of brain tumor diagnosed in dogs according to the literature. The affected animal was advanced in age, a factor that is associated with an increased risk of developing this neoplasm. The neurological alterations noted in this report were associated with the neoplastic process. The macroscopic finding of a cerebral neoformation was suggestive of neoplasm; this was confirmed by microscopic evaluation of the mass<span style="font-size: 12pt; line-height: 200%; font-family: ’Times New Roman’, serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">. As has been previously reported, the clinical neurological signs of most cases of suspected brain tumors occur late in the disease process, at which point the neoplasm is already in an advanced stage of development. Thus, the prognosis of the affected animal is poor, as it was in this case, which leads to euthanasia.In summary, this is a report of a case of intracranial transitional meningioma accompanied by progressive neurological alterations, in which an ante mortem diagnosis is difficult due to the limited use of computerized tomography in routine veterinary practice.